2022
DOI: 10.3390/healthcare10050855
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Fibroids and Pregnancy: A Review of the Challenges from a Romanian Tertiary Level Institution

Abstract: Background and Objectives. Uterine fibroids are relatively common in reproductive-age women and are directly linked to pregnancy. There are many debates about performing a myomectomy at the same time as a caesarian section (CS) in such cases due to the risk of a hemorrhage. Our study aims to investigate fibroid features and their evolution in pregnancy, complications of a myomectomy during CS and maternal and fetal obstetric outcomes of pregnancies with fibroids. Materials and methods. We realize a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…As per the largest study done of fibroids complicating pregnancy in Romanian tertiary care hospital in 2022, vaginal delivery were in 7% of the cases, with caesarean delivery in 85.96%.68% were diagnosed in the first trimester and the myomectomy rate was 24.48%. 4 In case 5, the fibroid was an incidental finding which was not recognised in scan. Successful myomectomy was achieved without further post operative complications.…”
Section: Discussionmentioning
confidence: 90%
“…As per the largest study done of fibroids complicating pregnancy in Romanian tertiary care hospital in 2022, vaginal delivery were in 7% of the cases, with caesarean delivery in 85.96%.68% were diagnosed in the first trimester and the myomectomy rate was 24.48%. 4 In case 5, the fibroid was an incidental finding which was not recognised in scan. Successful myomectomy was achieved without further post operative complications.…”
Section: Discussionmentioning
confidence: 90%
“…There was no growth or decrease in myoma size in any of them. In contrast with Benaglia et al, who, in their prospective cohort research on 25 women with fibroids, reported that the sizes of the fibroids dramatically increased to more than double their original sizes during the first seven weeks of pregnancy, Tîrnovanu et al observed change in the maximal rise occurred in the second trimester [ 10 , 17 ]. Nevertheless, Rosati et al discovered that up to 78% of uterine fibroids do not demonstrate significant growth during pregnancy [ 18 ].…”
Section: Discussionmentioning
confidence: 92%
“…Physical inspection can only detect big fibroids, and ultrasound's capacity to identify fibroids in pregnancy is even more limited due to the foetus [ 9 ]. Hence, the prevalence of uterine fibroids during pregnancy is underestimated [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Các giả thuyết được đưa ra: đầu tiên u xơ có thể cản trở quá trình hình thành bánh rau và phát triển tuần hoàn tử cung bình thường, thường gặp ở những khối u xơ dưới niêm mạc lớn nhô vào trong buồng tử cung. Thứ hai sự phát triển nhanh chóng của u xơ có hoặc không có sự thoái hóa dẫn tới tăng co bóp tử cung gây sảy thai [6]. Tuy nhiên, trong một phân tích tổng hợp của 9 nghiên cứu trên 21829 thai kỳ bao gồm 1394 đối tượng có u xơ tử cung và 20435 đối tượng còn lại không có, khi không xem xét vị trí của u xơ thì không tìm thấy mối liên quan giữa sự hiện diện của u xơ tử cung và sảy thai [7].…”
Section: Triệu Chứng Lâm Sàng Và Các Biến Chứng Liên Quan U Xơ Tử Cun...unclassified